KARAKTERISTIK ARANG AKTIF TANDAN KOSONG KELAPA SAWIT YANG DIIMPREGNASI LOGAM NIKEL SEBAGAI KATALIS - Rina Novia Yanti (Jurnal Penelitian Hasil Hutan, 2025)
Activated charcoal from biomass can be used for various applications because its high porosity. One of the utilization for activated charcoal as catalyst raw material from empty palm oil bunches. This study aimed to determine the characteristics of activated charcoal with nickel (Ni) impregnation as catalyst raw material in the upgrading bio-oil. Activated charcoal used 10%, 15%, and 20% H3PO4 was immersed for 24 hours, and calcinated at temperature of 750°C with steam activation time for 60 minutes. The optimum of the manufacturing of activated charcoal with with 10% H3PO4 , then impregnated with nickel in various concentration: 1%, 2%, and 3%. Results showed the characteristic of nickel impregnated activated charcoal were as follows: iodine absorbance capacity 554–756 mg/g, methylene blue absorbance capacity 38–90 mg/g, surfaces area 96–218 m2/g and pore diameter of 8.48–16.21 micron meter.